Search for K0S(L) → [mu]+ [mu]− [mu]+ [mu]− decays at LHCb - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kopecná, Renata; Leverington, Blake; Li, Peilian; et al. (Physical review, 2023)
A search for 𝐾0S⁡(L) →𝜇+⁢𝜇−⁢𝜇+⁢𝜇− decays is performed using proton-proton collision data collected by the LHCb experiment at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 5.1  fb−1. No evidence for signal is found. The 90% confidence level upper limits are the first set for both decays and are ℬ⁡(𝐾0S→𝜇+⁢𝜇−⁢𝜇+⁢𝜇−) <5.1 ×10−12 and ℬ⁡(𝐾0L→𝜇+⁢𝜇−⁢𝜇+⁢𝜇−) <2.3 ×10−9.
Gesehen am 28.02.2025
Im Titel ist die Zahl 0 und die Plus- und Minuszeichen hochgestellt sowie die Buchstaben S und L tiefgestellt
*LHCb Collaboration: R. Aaij, S. Bachmann, M. Borsato, R. Caspary, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, J. Marks, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und 1050 weitere Personen]